THE DYNAMICS OF INDONESIAN YOUTH ENGAGEMENT IN THE CONFERENCE OF THE PARTIES CLIMATE CHANGE CONFERENCE - Hastira, Muhammad Fajhriyadi; Riyanto, Sugeng; Khairullah, Septi (JURNAL ILMU SOSIAL, 2025)
This study examines the dynamics of the role and impact of the involvement of Indonesian youth delegates in the COP25–COP29 Climate Change Conferences through the lens of Two-Track Diplomacy. A descriptive qualitative method was employed, combining semi-structured interviews with six key informants and a literature analysis of scientific articles obtained from reputable databases such as Scopus, ScienceDirect, and DOAJ, as well as official reports from the UNFCCC, YOUNGO, and position papers released by the Indonesian youth delegation during COP. This study identifies how youth leverage informal diplomatic channels (Track II) to support and strengthen official negotiations (Track I). The findings indicate the presence of three primary mechanisms: (1) capacity building through climate negotiation simulations and literacy; (2) policy bridging by integrating data from affected communities into policy documents; and (3) transnational networking connecting YOUNGO, NGOs, and digital platforms. This simultaneous approach effectively promoted the adoption of several youth recommendations into Indonesia's Enhanced NDC 2022. However, structural challenges and tokenism continue to hinder the full effectiveness of their influence. These findings underscore the significance of implementing Two-Track Diplomacy as an integrative framework to bolster the representation and strategic impact of the younger generation in global climate diplomacy.